Numerical Analysis of Velocity Magnitude on Wave Energy Converter System in Perforated Breakwater - Oki Setyandito; Nizam Nizam; Andrew John Pierre; Gede Dharma Suputra; Yureana Wijayanti; Martin Anda (International Journal of Renewable Energy Development, 2022)
Waves are an alternative energy source that can be used for electricity generation. Wave Energy Converter (WEC) system in perforated breakwater is potentially applicable WEC system for coastal area. The magnitude of wave energy generated is determined by the volume of sea water inside the perforated breakwater. This volumetric flow rate is calculated using the flow velocity at perforated holes on the structure slope. Therefore, this research aims to study the velocity magnitude by analyzing the interrelation among wave steepness, wave run-up and relative velocity. The method used consists of applying numeric 3D flow model in the perforated structure of the breakwater with the variation of wave height, wave period and structure slope. The result shows that, the steeper the structure, the bigger is the relative run up (Ru/H). The higher the relative run up, the higher are the relative run-up velocities (V/Vru). As the velocity increase, the volumetric flow rate inside perforated breakwater will be higher, which leads to higher wave energy. Hence, it can be concluded that the higher the velocities (V/Vru), the higher is the wave energy generated.